Medication errors and adverse drug events: Analysis from perioperative anesthetic adverse events in Thailand (PAAD Thai study) - Surunchana Lerdsirisopon (2018)
© 2018, Medical Association of Thailand. All rights reserved. Objective: Perioperative medication administration can lead to the higher rate and severity of medication errors (MEs). This epidemiological study aimed to assess the current situation in Thailand regarding the frequency, types, severity, contributing factors and suggested corrective strategies of MEs related to anesthesia care. Materials and Methods: The prospective multi-center observational study was conducted in 22 university and non-university hospitals across Thailand. Data were collected during January 1 and December 31, 2015. MEs incidents were reported and filled out in the standardized incident reporting form on an anonymous and voluntary basis. All completed forms of MEs related to anesthesia were reviewed and discussed by peer reviewers who used the “Medication Error Detection Framework” to identify type of MEs, contributing factors and suggestive prevention strategies. Results: There were 85 relevant reports of MEs from the first 2,206 incident reports (4.25% of all incident reports). Overdosage (25 incidents, 29.4%) was the most frequently found types of error. 10 incidents (40%) occurred in pediatric patients. Wrong drug administration (19 incidents, 22.4%) was the second frequently found type of error including syringe swaps or wrong ampule. Labelling errors were reported for 15 events (17.6%). 16 incidents (18.8%) were caused temporary patient harm or prolong hospital stay. All of the incidents were related to human error and considered preventable. Conclusion: 4.25% of MEs were reported in our study, which comparable to the previous report from Thailand in 2007. Overdosage was the most frequently found type of errors. Pediatric patients were considered a high risk group. All of the incidents were related to human error and considered preventable. Vigilance and experience were factors that can help to minimize incidents.